Morphological characteristics and anatomical features of the perennial herb Ajania fastigiata (C. Winkl.) Poljakov (Asteraceae) - Amеrtayeva, G.A.; Mamurova, A.T.; Osmonali, B.B. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Medicinal plants are currently the most relevant objects of research. Since the final product that is obtained from useful plants belongs to the most valuable medicines. Particularly interesting plants in medicine are those containing essential oils, for example, species of the genus Artemisia, but few people know that closely related species of the genus Ajania are also rich in essential oils. The genus Ajania belongs to the Asteraceae family. Only 2 species of this genus are found in Kazakhstan: Ajania fruticulosa (Ledeb.) Poljak (shrub) and Ajania fastigiata (C. Winkl.) Poljak (perennial plant).Our object of research is Ajania fastigiata, which is distributed throughout the mountainous territory of the Southern and Southeastern regions of the Republic of Kazakhstan. It is little studied in terms of precise morphological and anatomical features, knowledge of which makes it possible to quickly determine and refine the species. The nearest point in the Trans-Ili Alatau was chosen for the prototype. The research methods were classical botanical and anatomical. When analyzing the approximate population, the morphological data of the species for this territory were clarified. Anatomical studies have shown that the leaves of Ajania fastigiata contain essential oil glands and receptacles for metabolic products. The stems of this species have a characteristic arrangement of sclerenchyma in separate strands.
Ajania fastigiata (C. Winkl.) Poljakov (Asteraceae) көпжылдық дәрілік өсімдігінің морфологиялық сипаттамасы және анатомиялық ерекшеліктері
Морфологическая харектеристика и анатомические особенности многолетнего лекарственного растения Ajania fastigiata (C. Winkl.) Poljakov (Asteraceae)
Keywords: Asteraceae; Ajania fastigiata; morphology; anatomy; medicinal plants; essential oils; systematic features; Trans-Ili Alatau